Factors determining market prices of small ruminants from a pastoral production system in Kenya - Chabari, F.N.; Ackello-Ogutu, A.C.; Odhiambo, M.O. (1987)
Reports on the results of a study of small ruminant marketing from a pastoral production system in Baringo district (northern Kenya). Estimates the effects of body weight, body condition, species, sex and time of sale. Evaluates the effectiveness of the auction method in stabilizing prices during a selling operation.